1989
DOI: 10.3109/03009748909102106
|View full text |Cite
|
Sign up to set email alerts
|

Low Power Laser Therapy of Shoulder Tendonitis

Abstract: 30 patients with supraspinatus or bicipital tendonitis were randomly allocated to active infrared laser therapy at 904 nm three times weekly for 2 weeks, dummy laser or drug treatment for 2 weeks. Objectively maximum active extension, flexion and abduction of the shoulder, and subjectively pain stiffness movement and function were measured at 0 and 2 weeks. Significant improvement of active over dummy laser was noted for all seven assessments. Active laser therapy produced significant improvement over drug the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0
5

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(74 citation statements)
references
References 16 publications
1
67
0
5
Order By: Relevance
“…Of the 14 randomized clinical trials evaluating LLLT, two were discarded due to inadequate controls. Of the remaining studies, five showed improvement treating tendinopathy with LLLT compared to placebo LLLT [23,52,90,170,171], while seven studies showed no difference [16,21,69,87,101,184,186]. Four systematic reviews have addressed LLLT and all agreed the best current level of evidence does not support its use in the treatment of tendinopathy [65,106,168,181].…”
Section: Other Modalitiesmentioning
confidence: 99%
“…Of the 14 randomized clinical trials evaluating LLLT, two were discarded due to inadequate controls. Of the remaining studies, five showed improvement treating tendinopathy with LLLT compared to placebo LLLT [23,52,90,170,171], while seven studies showed no difference [16,21,69,87,101,184,186]. Four systematic reviews have addressed LLLT and all agreed the best current level of evidence does not support its use in the treatment of tendinopathy [65,106,168,181].…”
Section: Other Modalitiesmentioning
confidence: 99%
“…supraspinatus ve bisipital tendinitli 30 hastaya Ga-As lazer (904 nm dalga boyunda 5 dakika, haftada 3 kez olmak üzere 6 seans), naproksen sodyum (550 mg/gün, 2 hafta boyunca) ve plasebo lazer tedavisi uygulamışlar; lazerin ağrı ve hareket genişliğini arttırmada plasebo lazer ve naproksen sodyuma göre daha üstün olduğunu bulmuşlardır. 34 Vecchio ve ark. 35 rotator tendinitli hastayı 2 gruba ayırmışlar, 1. gruba lazer (5000 Hz frekans, 830 nm dalga boyu, 30 mw galyum-arsenik diod laser, günde 10 dakika, haftada 2 kez, 8 hafta süre ile toplam 9 tedavi) ve denetimli egzersiz, 2. gruba; plasebo lazer ve denetimli egzersiz uygulamışlar, ayrıca her 2 gruba sarkaç egzersizleri ve EHA için duvar tır-manma egzersizleri vermişlerdir.…”
Section: Discussionunclassified
“…In another study [9]among 30 patients with shoulder tendonitis, the low power infrared LA-SER therapy of 904nm was found to be effective in getting a statistically significant improvement various parameters such as maximum active extension, flexion, abduction of shoulder; subjective pain; subjective stiffness with movement; and the functions. The improvement was seen in 6 sessions over a period of 2 weeks.…”
Section: Resultsmentioning
confidence: 99%